2022
DOI: 10.3390/antiox11081437
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside as a Potential Natural Product Targeting Oxidative Stress in Liver Diseases

Abstract: Hyperoside (Hyp), also known as quercetin-3-O-galactoside or 3-O-β-D-galactopyranosyl, is a well-known flavonol glycoside that is abundant in various fruits, vegetables, and medicinal plants. Hyp has been suggested to exhibit a wide range of biological actions, including cardiovascular, renal, neuroprotective, antifungal, antifibrotic, and anticancer effects. Accumulating evidence supports the pharmacological activities of Hyp in improving liver pathophysiology. Hence, the present literature review aims to sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The antioxidant activity of HP is likely intricately linked to its chemical composition, primarily contingent upon the primary structure and positioning of the galactose sugar moiety attached to this compound. Its effectiveness is impacted by the presence of galactose at position C-3 and the β-hydroxyl groups at C-3′ and C-4′, highlighting the significance of the antioxidant structure–activity relationship ( Jang, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of HP is likely intricately linked to its chemical composition, primarily contingent upon the primary structure and positioning of the galactose sugar moiety attached to this compound. Its effectiveness is impacted by the presence of galactose at position C-3 and the β-hydroxyl groups at C-3′ and C-4′, highlighting the significance of the antioxidant structure–activity relationship ( Jang, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has the potential to operate antioxidant activity to prevent hepatic oxidative stress in liver diseases. Te hydrogen peroxide-induced intracellular oxidative damage in HepG2 cell lines demonstrated the antioxidative efects of hyperoside [49]. Notably, in the presence of hyperoside, the modulation of hepatic mitogen-activated protein kinase, heme-oxygenase-1, nuclear factor erythroid 2-related factor 2, and may augment antiapoptosis and ultimately prevent chemically-driven hepatotoxicity in mice [50].…”
Section: In Vivo and In Vitro Studies Numerous Studies Havementioning
confidence: 97%
“…Nevertheless, kaempferol and hyperoside were found in the DE. Previous research has reported that hyperoside exhibits a wide range of pharmacological effects, including antioxidant activity, anti-cancer activity, neuroprotective activity, antimicrobial activity, and anti-inflammatory activity [47,48]. It can decrease the intracellular reactive oxygen species (ROS) levels and lipid peroxidation in Saccharomyces cerevisiae [49].…”
Section: Antioxidant Activity Of C Chinensis Seed Extractsmentioning
confidence: 99%